Pitha or plinth of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
Details of the base mouldings of the Suswani Mata Temple. Four mouldings of the vedibandha (basal mouldings) are visible- from bottom to top khura (hoof), kumbha (pot), kalasha (pitcher), kapotali (cyma recta). There are floral motifs on the front face of the kumbha moulding.